КОМПЬЮТЕРНОЕ МОДЕЛИРОВАНИЕ ЭЛЕКТРОТЕПЛОВЫХ ПРОЦЕССОВ И ТЕРМОМЕХАНИЧЕСКИХ НАПРЯЖЕНИЙ ПРИ ИНДУКЦИОННОМ НАГРЕВЕ ДВИЖУЩИХСЯ МЕДНЫХ СЛИТКОВ - Щерба, А.А.; Подольцев, А.Д.; Кучерявая, И.Н.; Ушаков, В.И. (Інститут електродинаміки НАН України, Київ, 2013)
A computing technique is developed to determine and study the electromagnetic and thermal processes as well as thermomechanical stress at induction heating of cylindrical ingots continuously moving in alternating magnetic field of long inductor. The technique is based on finite-element method realized in program Comsol. The comparative analysis of ingot heating is carried out for different frequencies of supply source and for two cases: 1) at available laminated core that adjoins to external side of cylindrical inductor; 2) without core. As shown, the maximum value of thermomechanical stress in the ingot is on its surface at outlet from the inductor. At given inductor length (6 m) this value does not exceed ultimate strength of the material. References 11, figures 8.